Management of arterial injury during endoscopic sinus and skull base surgery. Issue 2 (April 2016) - Valentine, Rowan; Padhye, Vikram; Wormald, Peter-John
Abstract : Purpose of review: The most feared complication during endonasal surgery is a carotid artery injury. The sheep model of carotid injury provides training for this event by giving a realistic endoscopic experience of major vascular injuries and tissue hemostasis. Recent findings: The sheep model of carotid artery injury recreates the narrow nasal confines and high-flow/high-pressure vascular injury accurately reproducing the endoscopic challenges seen in such vascular emergencies. This has led to the development of surgical techniques that quickly and effectively control the field of bleeding and achieve reliable hemostasis including the crushed muscle patch new direct vascular closure technologies. Vascular emergency simulation training is achieving better outcomes for our patients. Summary: All skull base surgeons are at risk of the unexpected carotid artery injury and recently, the sheep model not only effectively recreates this situation but has identified clinically tried and tested techniques at managing this situation and is improving patient outcomes.